Different sources of mycosporine-like amino acids: Natural, heterologous expression, and chemical synthesis/ modifications - Fariba Fathi; Tahereh Hosseinabadi; Amirhossein Faraji; Maryam Tabarzad (Future Natural Products, 2022)
Background and aims: Due to the increasing incidence of skin cancer and other skin disorders caused by ultraviolet (UV) irradiation, development of more efficient sunscreens seems to be essential. Mycosporine-like amino acids (MAAs) are one group of the natural UV absorbent compounds with sunscreen characteristics that have been the focus of a number of researches. This article aims to introduce different sources of MAAs in order to discuss pros and cons in finding the best way for high-scale MAAs production. Methods: Scientific databases and search engines including Science Direst and Google Scholar were investigated using “Mycosporine-like amino acid” AND “Production” as main keywords. Results: An increasing number of publications have been published regard to MAAs in recent 10 years. Publications showed that a wide range of organisms can produce these UV-absorbing compounds, especially under stressful and extreme conditions. Numerous studies has been performed to identify the pharmaceutical and cosmeceutical applications of MAAs. However, it is still challenging to choose the best source for the large-scale production of these compounds. Direct MAAs extraction from natural sources, heterologous production of MAAs using recombinant DNA technology or metabolic engineering, and a few studies of chemical synthesis of MAA derivatives have been reported, so far. Conclusion: Among various reports, direct extraction from the natural source has got the main position, until now. However, there is an increasing interest on the recombinant production of MAAs in new hosts, with more appropriate features for large-scale production. Nevertheless, it also seems that the chemical synthesis of these compounds is not affordable.